Field‐Effect Transistors: Contact‐Engineered Electrical Properties of MoS2 Field‐Effect Transistors via Selectively Deposited Thiol‐Molecules (Adv. Mater. 18/2018). Issue 18 (2nd May 2018) - Cho, Kyungjune; Pak, Jinsu; Kim, Jae‐Keun; Kang, Keehoon; Kim, Tae‐Young; Shin, Jiwon; Choi, Barbara Yuri; Chung, Seungjun; Lee, Takhee
Abstract : A simple contact‐engineering method, which introduces chemically adsorbed thiol‐molecules as thin tunneling barriers between the metal electrodes and MoS2 channels, is proposed by Seungjun Chung, Takhee Lee, and co‐workers in article number1705540 . The selectively deposited thiol‐molecules provide additional tunneling paths at the contact regions, improving the carrier injection with lower activation energies in MoS2 field‐effect transistors. Furthermore, asymmetric carrier‐injection is feasible by inserting thiol‐molecules at only one contact region.